An Analysis of Slang Word Formation in Ice Cracker Ii (The Emperor’s Edge 1.5) Short Story by Lindsay Buroker - Hardianti Hardianti; Fina Amalia Masri (ELITE: Journal of English Language and Literature, 2017)
This research used Short Story by Lindsay Buroker as the object material and Slang Word Formation by George Yule’s as a theory. This research aimed to analyze what is the slang word formation in Ice Cracker II (The Emperor’s Edge 1.5) Short Story. This research used a qualitative research method. The result of the research shows that there are 11 data found, they are Coinage consists of 2 data, Compounding consists of 2 data, Blending consists of 3 data, Clipping consist of 1 data, Derivation consists of 2 data, and Multiple Process consist of 1 data. The most dominant of slang word formation is Blending. Blending is a combination of two separate word forms to make a single new word term.